The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/la2011259
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Conjugated Nanobubbles for Targeted Ultrasound Molecular Imaging

Abstract: Targeted ultrasound contrast agents can be prepared by some specific bioconjugation techniques. The biotin-avidin complex is an extremely useful noncovalent binding system, but the system might induce immunogenic side effects in human bodies. Previous proposed covalently conjugated systems suffered from low conjugation efficiency and complex procedures. In this study, we propose a covalently conjugated nanobubble coupling with nucleic acid ligands, aptamers, for providing a higher specific affinity for ultraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 32 publications
0
55
0
Order By: Relevance
“…For example, Lanza et al used a 30MHz intravascular ultrasound system to detect thrombi with a targeted perfluorocarbon emulsion based contrast agent (250nm) 22 . Wang et al used a custom-made 40MHz transducer to image nanobubbles (485nm) targeting to CCRF-CEM cells in an ex vivo model 23 . Efforts have also been made to decrease the shell stiffness by incorporating surfactant in order to decrease the detection frequency for nanobubbles, as described in detail below 18 .…”
Section: Physics and Theory Behind Ultrasound And Its Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lanza et al used a 30MHz intravascular ultrasound system to detect thrombi with a targeted perfluorocarbon emulsion based contrast agent (250nm) 22 . Wang et al used a custom-made 40MHz transducer to image nanobubbles (485nm) targeting to CCRF-CEM cells in an ex vivo model 23 . Efforts have also been made to decrease the shell stiffness by incorporating surfactant in order to decrease the detection frequency for nanobubbles, as described in detail below 18 .…”
Section: Physics and Theory Behind Ultrasound And Its Contrast Agentsmentioning
confidence: 99%
“…Although the mechanism is not fully understood, it has been postulated that the shell bending modulus resists increases in curvature below 1 μm, producing only a small number of nanobubbles 39 . Nanobubble formulations have thus been obtained by extraction of this nanometer subpopulation from microbubble solutions based on their buoyancy by centrifugation 23, 40-45 . Although this method produces a relatively small nanobubble yield, it has been demonstrated that these nanobubbles are capable of extravasating the leaky vasculature in tumors and improving signal intensity under diagnostic ultrasound 42-44 .…”
Section: Next Generation Nano Agents In Cancer Detectionmentioning
confidence: 99%
“…The use of nanobubbles [29,[278][279][280][281][282][283][284][285][286] as US contrast agents is in constant progress. Even if named nanobubbles they are typically in the range 150 to 1000-nm in diameter.…”
Section: Ultrasound (Us)mentioning
confidence: 99%
“…Regardless of composition, surface functionalization of the nanomaterial is required to enable targeting and stealth for long circulation times with minimal nonspecific binding [239]. There is a plethora of entities that can be incorporated onto a NP's surface, with covalent bonding preferred over electrostatic interactions: DNA, RNA, [472] oligonucleotides (aptamers), [29,434,[473][474][475][476] peptides, [36,175,201,[477][478][479][480][481][482] proteins, [483][484][485][486][487] enzymes, [488][489][490][491] antibodies [492]. No matter what the surface moiety, its activity must not be altered once anchored to the NP surface ( Figure 13).…”
Section: Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation